1977
DOI: 10.1121/1.381433
|View full text |Cite
|
Sign up to set email alerts
|

Property detectors for bursts and transitions in speech perception

Abstract: A series of adaptation experiments was conducted to investigate the role of initial noise bursts and transitions as cues to place of articulation in stop consonants. A test continuum was constructed consisting of 14 synthetic stimuli in which 'the transitions of formant two and formant three were systematically varied to range along the [b dg] phonetic dimension. The adapting stimuli consisted of full-cue stimuli in which place of hrticulation was signaled by burst as well as transitions; partial-cue stimuli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
3
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
0
26
3
1
Order By: Relevance
“…With most /da/ sounds, there is an F2 formant onset, followed by its transition. Contrary to the conclusions of Cooper et al (1952); Cole and Scott (1974a); Dorman et al (1977) and Blumstein et al (1977), this F2 onset can cause a forward masking effect on the formant transition, and thus, in that case, the F2 would play no role in perception. If a burst of energy is present immediately before the formant onset (around 2 [kHz], before vowel onset), the entire formant transition may be forward masked, and the onset plays no role in perception.…”
Section: /Da/contrasting
confidence: 41%
See 1 more Smart Citation
“…With most /da/ sounds, there is an F2 formant onset, followed by its transition. Contrary to the conclusions of Cooper et al (1952); Cole and Scott (1974a); Dorman et al (1977) and Blumstein et al (1977), this F2 onset can cause a forward masking effect on the formant transition, and thus, in that case, the F2 would play no role in perception. If a burst of energy is present immediately before the formant onset (around 2 [kHz], before vowel onset), the entire formant transition may be forward masked, and the onset plays no role in perception.…”
Section: /Da/contrasting
confidence: 41%
“…The same year, Blumstein et al (1977) published a related /b,d,g/ study, using synthetic speech, that also presented a look at the burst and a host of transition cues. They explored the possibility that the cues were integrated (acted as a whole).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence seems to indicate that the position can have a greater adaptation effect than partial cue adapters (Blumstein et al, 1977). Therefore, if the same detectors process initial and final place of articulation cues in a vev context, then the full cue adapters may have a greater effect than the partial cue adapters.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that bursts are processed at the level affected by selective adaptation (Blumstein, Stevens, & Nigro, 1977;Diehl, 1975). IiiExperiment 1, synthetic CV and VC series were constructed in which place of articulation was cued by the burst as well as the second-and third-formant transitions.…”
mentioning
confidence: 99%
“…Other attempts to dissociate acoustics from phonetics (e.g., Blumstein, Stevens, & Nigro, 1977 Blumstein et al con-cluded that the adaptation effect was "based upon the acoustic information in the signal rather than the phonetic label given the stimulus by the subject" (p. 1310). However, the remaining three subjects identified this same conflicting cue adaptor as [da], suggesting that the acoustic/phonetic dissociation in this instance was not perfect.…”
mentioning
confidence: 99%